Access and coverage: which farmers do plant clinics reach in Uganda?. Issue 8 (17th November 2017) - Karubanga, Gabriel; Matsiko, Frank B.; Danielsen, Solveig
ABSTRACT: This article reports on a study that assessed farmers' access to, and coverage of, five plant clinics operating from market places in two districts of Uganda. Despite the noticeable geographic and thematic coverage of the services, placing plant clinics at markets did not automatically ensure equitable access and high farmer attendance. Clinic users were predominantly middle-aged male farmers and overall attendance was relatively low. Uganda has taken plant clinics to scale in recent years due to their potential to strengthen the country's responsiveness to pests and diseases. Optimising farmer reach and ensuring equity in access requires reviewing clinic placement, timing, and mobilisation strategies.